Influence of magnetic field and stellar radiative feedback on the collapse and the stellar mass spectrum of a massive star-forming clump - Hennebelle, Patrick; Lebreuilly, Ugo; Colman, Tine; Elia, Davide; Fuller, Gary; Leurini, Silvia; Nony, Thomas; Schisano, Eugenio; Soler, Juan D.; Traficante, Alessio; Klessen, Ralf S.; Molinari, Sergio; et al. (Astronomy and astrophysics, 2022)
Context. In spite of decades of theoretical efforts, the physical origin of the stellar initial mass function (IMF) is still a subject of debate.Aims. We aim to gain an understanding of the influence of various physical processes such as radiative stellar feedback, magnetic field, and non-ideal magneto-hydrodynamics on the IMF.Methods. We present a series of numerical simulations of collapsing 1000 M⊙ clumps, taking into account the radiative feedback and magnetic field with spatial resolution down to 1 AU. We performed both ideal and non-ideal MHD runs, and various radiative feedback efficiencies are considered. We also developed analytical models that we confront with the numerical results.Results. We computed the sum of the luminosities produced by the stars in the calculations and it shows a good comparison with the bolometric luminosities reported in observations of massive star-forming clumps. The temperatures, velocities, and densities are also found to be in good agreement with recent observations. The stellar mass spectrum inferred for the simulations is, generally speaking, not strictly universal and it varies, in particular, with magnetic intensity. It is also influenced by the choice of the radiative feedback efficiency. In all simulations, a sharp drop in the stellar distribution is found at about Mmin ≃ 0.1 M⊙, which is likely a consequence of the adiabatic behaviour induced by dust opacities at high densities. As a consequence, when the combination of magnetic and thermal support is not too high, the mass distribution presents a peak located at 0.3-0.5 M⊙. When the magnetic and thermal support are high, the mass distribution is better described by a plateau, that is, dN/dlog M ∝ M−Γ, Γ ≃ 0. At higher masses, the mass distributions drop following power-law behaviours until a maximum mass, Mmax, whose value increases with field intensity and radiative feedback efficiency. Between Mmin and Mmax, the distributions inferred from the simulations are in good agreement with an analytical model inferred from gravo-turbulent theory. Due to the density PDF ∝ρ−3/2 relevant for collapsing clouds, values on the order of Γ ≃ 3/4 are inferred both analytically and numerically. More precisely, after 150 M⊙ of gas have been accreted, the most massive star has a mass of about 8 M⊙ when magnetic field is significant, and 3 M⊙ only when both the radiative feedback efficiency and magnetic field are low, respectively.Conclusions. When both the magnetic field and radiative feedback are taken into account, they are found to have a significant influence on the stellar mass spectrum. In particular, both of these effects effectively reduce fragmentation and lead to the formation of more massive stars.